PENGARUH PENAMBAHAN TEPUNG RUMPUT LAUT (EUCHEUMA COTTONII) SEBAGAI BAHAN PENSTABIL TERHADAP KARAKTERISTIK FISIK DAN HASIL UJI SENSORI ES KRIM - Rita Purwasih; Enceng Sobari; Qurrota ‘Ayun Nurhasanah (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The purposes of the research are to determine the physical characteristics (overrun, emulsion stability and melting power) in ice cream, learn the effect of adding seaweed flour to the results of sensory test (hedonic test and descriptive test) on ice cream and know the best treatment for ice cream with the addition of seaweed flour. The design of the analysis used is completely randomized design (CRD) with addition of seaweed flour 0%; 0,2%; 0,4%; 0,6% and 0,8%. Data processing used the One Way ANOVA method, and Duncan Multiple Range Test (DMRT) method at a significant level of 5% (P ≤ 0,05). Based on the results of the analysis of the physical characteristics of ice cream that have been in accordance with the SNI, the melting power is found in treatments R1, R2, R3 and R4. Overrun values that are in accordance with SNI are treatment R0 and R1, with the highest emulsion stability found in treatment R0. The addition of seaweed flour to ice cream did not have a significant effect (P 0.05) on the hedonic test and descriptive test with texture, odor and flavor on ice cream. The overall best treatment based on the level of preference for the panelists was the R1 treatment with the addition of 0.2% seaweed flour.